A study of double functions and load matching of a phosphoric acid fuel cell/heat-driven refrigerator hybrid system. (15th April 2016) - Chen, Xiaohang; Wang, Yuan; Zhao, Yingru; Zhou, Yinghui
Abstract: A generic model of the hybrid system consisting of a phosphoric acid fuel cell (PAFC) and a heat-driven refrigerator is originally established. On the basis of the models of PAFCs and three-heat-source refrigerators, the equivalent power output and efficiency of the hybrid system are obtained. The performance characteristic curves of the hybrid system are plotted through numerical calculation, showing that the performance of the hybrid system in the whole operating region is better than that of a single PAFC. The maximum equivalent power output density and the corresponding efficiency of the hybrid system are calculated. It is found that compared with the maximum power output density and the corresponding efficiency of a single PAFC, the maximum equivalent power output density of the hybrid system increases 938 W/m 2 and the equivalent efficiency of the hybrid system at the maximum equivalent power output density increases 5.86%. The optimal ranges of the equivalent efficiency of the hybrid system and the current density of the PAFC are determined. The effects of the refrigeration temperature on the performance of the hybrid system are discussed in detail. Two different loads of the hybrid system are optimally matched. Highlights: A new phosphoric acid fuel cell/refrigerator hybrid system is proposed. The optimum performance characteristics of the system are revealed. The effects of the refrigeration temperature on the performance are discussed. Two different loads of the system are optimally matched. The double functions of the power output and refrigeration are realized.